Sosialisasi Program Si Gempi : Komik Edukasi Hukum Cambuk Berbasis AR 3D Sebagai Solusi Pencegahan Jarimah di SMAN 1 Kuta Makmur - Desy Fatmasari; Desi Periati; Nawang Wulandari; Zahra Aziqah; Muhammad Fathi Annaqi (Jurnal Pendidikan Indonesia, 2025)
Aceh as a province with special autonomy enforces Qanun Aceh Number 6 of 2014 concerning the Jinayat Law which regulates various violations of Islamic sharia (jarimah). However, the level of public understanding, especially teenagers, of the whipping law is still low. Based on a survey at SMA Negeri 1 Kuta Makmur, as many as 70% of students do not know the legal basis of whipping and the other 30% only know in general without understanding its substance. This condition encourages the implementation of the Si Gempi Program, which is the socialization of the law of whipping through educational comic media based on Augmented Reality (AR) 3D technology as an interactive and contextual means of learning. The method of implementing the activity included lectures, discussions, practices, and mentoring involving two lecturers, six teachers, and forty students. This program was carried out at SMA Negeri 1 Kuta Makmur with several stages, namely the delivery of material about Qanun Jinayat and juvenile delinquency, the introduction of the Si Gempi comic based on AR 3D, as well as role play activities and digital creative assistance. The results of the activity showed an increase in students' understanding of Aceh's whipping law and Islamic sharia values, as well as fostering interest in technology-based legal literacy among teenagers. This program has the potential to be a model of digital-based legal education that is effective in supporting the prevention of jarimah among Aceh students.